Edukasi Anti Bullying Pada Siswa PKBM Negeri 34 Cipayung - Hesti Rosdiana; Lia Wulandari; R. Maisa Yudono (Compromise Journal Community Proffesional Service Journal, 2024)
The increase in bullying cases in recent years seems to indicate that the problem of bullying has not yet been resolved. In Indonesia, bullying is still a major problem that has not been resolved properly. Bullying, also known as bullying, is a person's behavior that is carried out deliberately and consciously by individuals or groups to other people with the aim of threatening, hurting and suppressing victims and is carried out repeatedly. Bullying can occur in the form of physical, non-physical, verbal, non-verbal, and through the realm of cyberspace. Bullying can also occur anywhere and by anyone, especially by children and adolescents in the school environment. Therefore, bullying prevention in the school environment needs to be done, one of which is through bullying education itself. With bullying education, students in schools are expected to understand bullying as a whole. The results of the education show that students not only understand bullying as a whole but also grow self-awareness from students to not want to commit acts of bullying in any form.